Long-term optimization of operating costs: an analysis of the US railways tests - D. A. Macheret; N. A. Valeev (Вестник Научно-исследовательского института железнодорожного транспорта)
Reformation of railway transport, one of the goals of which is to optimize transportation costs, should be based not only on improving the management system, but also on the combination of technical, technological and marketing innovations. Russian railways will benefit from the experience of reforming US Class I railroads - the largest railway system in the world, as a result of which specific operating costs were reduced by more than 3.5 times with a quantitative and qualitative growth in the transportation offers.The prerequisites for reforming the railway industry in the United States were deterioration of railways condition, decrease in the quality of service, a deficit in the car fleet and, as a result, a significant decrease in the share of rail transport in the freight turnover of the whole transport system.In a competitive market, the deregulation of the railway system has made it possible to reduce both the transportation tariffs and the costs of railway companies that are able to respond quickly to consumer preferences.Optimization of operating costs for vertically integrated railways in the United States was achieved through systemic growth in productivity of all types of resources: infrastructure, labor, rolling stock and fuel. Due to this it is provided a long-term cost optimization, rather than a tem-porary decline, followed by a compensatory growth.The main driver of efficiency growth was the introduction of technical/technological and organizational/managerial innovations, which resulted in the replacement of more available jobs with fewer high-tech jobs, which allowed to increase labor productivity by almost 5 times.At the same time, in the period from 2005 to 2015 there was a slowdown in the growth of quality indicators and even some of their decline, which was caused by the approach to the maximum in terms of technical and technological capabilities levels of intensity of resource use and, accordingly, depletion of reserves. Removing constraints on the growth of efficiency requires the activation of innovation activity with additional motivation for this based on market factors.The experience of the US railways requires careful consideration when solving the problems of increasing the efficiency of Russian railways, naturally, taking into account their inherent economic and technical-technological characteristics.